Akarotaxis gouldae, a new species of Antarctic dragonfish (Notothenioidei: Bathydraconidae) from the western Antarctic Peninsula - Corso, Andrew D.; Desvignes, Thomas; Mcdowell, Jan R.; Cheng, Chi-Hing Christina; Biesack, Ellen E.; Steinberg, Deborah K.; Hilton, Eric J. (Zootaxa, 2024)
Bathydraconidae (Notothenioidei) are a group of benthic fishes endemic to the Southern Ocean. Because of their recent evolutionary radiation and limited sampling efforts due to their occurrence in remote regions, their diversity is likely underestimated. Akarotaxis nudiceps, currently the only recognized member of its genus, is an especially poorly known bathydraconid. Although A. nudiceps has a circumpolar distribution on the Antarctic continental shelf, its deep habitat and rarity limit knowledge of its life history and biology. Using a combination of morphological and genetic analyses, we identified an undescribed species of this genus, herein named Akarotaxis gouldae sp. nov. (Banded Dragonfish). The separation of this species was initially identified from archived larval specimens, highlighting the importance of early life stage taxonomy and natural history collections. All currently known adult and larval A. gouldae sp. nov. specimens have been collected from a restricted 400 km coastal section of the western Antarctic Peninsula, although this is possibly due to sampling bias. This region is targeted by the epipelagic Antarctic krill fishery, which could potentially capture larval fishes as bycatch. Due to the extremely low fecundity of A. gouldae sp. nov. and near-surface occurrence of larvae, we suggest the growing Antarctic krill fishery could negatively impact this species.